Pemberdayaan Penjahit di Simpang Len dalam Memanfaatkan Kain Perca - Lailasari, Linda; Mursyidin, Mursyidin; Hasibuan, Paizah; Rahma, Intan Tri; Amelia, Ubratul; Fazilah, Rida (Journal of Politics, Governance, and Administration, 2025)
This community service program focuses on empowering tailors in Simpang Len by optimizing the utilization of fabric waste. Through training and mentoring, local tailors were taught to transform textile waste into marketable craft products such as bags, pillowcases, and accessories. The results showed a 60% reduction in textile waste and a significant increase in participants' income and technical skills. This initiative promotes sustainable circular economy practices while strengthening local economic empowerment and environmental awareness. Abstrak Program pengabdian masyarakat ini berfokus pada pemberdayaan penjahit di Simpang Len dengan mengoptimalkan pemanfaatan kain perca. Melalui pelatihan dan pendampingan, para penjahit lokal dilatih untuk mengubah limbah tekstil menjadi produk kerajinan bernilai jual seperti tas, sarung bantal, dan aksesori. Hasil kegiatan menunjukkan pengurangan limbah tekstil hingga 60% dan peningkatan signifikan dalam pendapatan serta keterampilan teknis peserta. Inisiatif ini mendorong praktik ekonomi sirkular berkelanjutan sekaligus memperkuat pemberdayaan ekonomi lokal dan kesadaran lingkungan.